Cegah Stunting dengan perbaikan Pola Makan, Pola Asuh dan Pola Hidup Bersih dan Sehat (PHBS) di UPT Puskesmas Kedai Durian Medan - Harefa, Rizka Fadhilah Zahra; Suriadi, Agus; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
Stunting poses a significant public health challenge in numerous countries, including Indonesia. Preventive efforts targeting stunting are paramount, with a proven effective approach involving the enhancement of dietary patterns, parenting practices, and adherence to clean and healthy living habits (CHLH). This article delves into the importance of interventions focusing on these three factors to prevent stunting, specifically within the Indonesian context. Recent data and findings are presented to bolster arguments advocating for behavioral and habitual changes necessary to combat the issue of stunting at both individual and societal levels. Understanding the multifaceted nature of stunting and its ramifications necessitates comprehensive strategies addressing dietary, caregiving, and hygiene practices. By emphasizing the significance of these interventions, this article underscores the urgency of collective action in promoting healthier lifestyles and ensuring optimal growth and development, particularly among vulnerable populations.